Comparing caudal and penile nerve blockade using bupivacaine in hypospadias repair surgeries in children - Mahin Seyedhejazi; Rasoul Azerfarin; Fahime Kazemi; Maryam Amiri (Wolters Kluwer Medknow Publications, 2011)
Background: Caudal anaesthesia is recommended for most surgical procedures of the lower part of the body, mainly below the umbilicus. It has been well established that a dorsal penile nerve block immediately after surgery decreases postoperative pain in children undergoing hypospadias repair. This study aimed to compare caudal or penile nerve block using bupivacaine in postoperative pain control in hypospadias repair in children. Patients and Methods: After local ethical committee approval and obtaining informed parental consent, 85 American society of Anesthesiologists status I and II patients, aged 6 months to 6 years old, undergoing hypospadias repair, were prospectively enrolled in this study. The patients were randomly divided into the following two groups: Caudal block was performed in 44 and penile block was performed in 41 patients. Cardiorespiratory systems data, analgesic requirement and complications were compared between the groups. Results: There were statistically significant haemodynamic (blood pressureand heart rate) alteration during operation in each group (P<0.01). The haemodynamic parameters were stable during operation in successful blocks in both groups. Caudal block success rate is 97.7%, whereas in penile block is 92.6%. Nineteen of 43 patients (44%) in caudal group and 29 of 41 patients (70%) in penile group received analgesia in the postoperative period and this difference was significant between the two groups (P = 0.025). Conclusions: Without ultrasonography and with blind block, with anatomic landmarks only, the caudal block success rate is high and if there is no contraindication for caudal block, it is the best choice in children under 6 years old (or 25 kg) for hypospadias repai.